Pengaruh Profesionalisme Kinerja Aparatur Pemerintah Kelurahan Terhadap Mutu Pelayanan Publik - Muhamad Fikri Irawan; Ilham Zitri; Muhammad Ali (Universitas Muhammadiyah Mataram, 2024)
Public service is a mandatory duty of the government apparatus as a public servant. This understanding implies that in carrying out their duties, they must always try to serve the interests of the community by complying with applicable regulations. The type and model of this research is a quantitative research model by analyzing data validity, data reliability and hypothesis testing. This study aims to examine whether there is an influence between the independent and dependent variables, namely between the variable Professionalism of the Village Government Apparatus Performance (X) on the quality of public services (Y) in Prapen Village, Praya District, Central Lombok Regency. The results of the study support the existence of a significant influence on the quality of public services, the professionalism of employee performance on the level of community satisfaction in Prapen Village, Praya District, Central Lombok Regency.